MENINGKATKAN HASIL BELAJAR SISWA BERBASIS MULTI INTELEGENSI PADA MATERI KELARUTAN DAN KESETIMBANGAN LARUTAN (Ksp) MELALUI MODEL INQUIRY TERBIMBING - Syailani Syailani (FKIP ULM, 2017)
Abstract. There has been a research in regards to the application of ‘guided inquiry model’ on the multi-intelligence based learning of the solution solubility and equilibrium in the 11th grade students of science in SMA Negeri 1 Banjarmasin. The study aimed to identify student’s achievement and response toward guided inquiry model on the topic of solution solubility and equilibrium. The research was a class-action research conducted in 2 cycles. Each cycle consisted of planning; action, observation and evaluation, analysis and reflection steps. The subject of the study are the 11th grade students of Science in SMA Negeri 1 Banjarmasin consisting of 22 students. The data was collected using test and observation. The result found that students’ achievement of chemistry especially on the solubility and equilibrium showed a significant improvement. The use of Guided Inquiry model improves students’ acvievement from 25% on the 1st cycle to 90% on the 2nd cycle. Student’s activities score improves from 47 on the 1st cycle to 52 on the 2nd cycle which both score stand for ’very active’. Teacher’s activities score on the learning improves from 49 on the 1st cycle to 52 on the 2nd cycle and both also stand for ’very active’. Students give very good response to the model. The use of the model gave a better students’ understanding to the topic and fully involved on learning. Students’ responsibility of doing assignment grow better. Students feel that the class was very pleasing, teacher was functioned as the facilitator or the advisor on learning. Keywords: guided inquiry, multi-intelligence, solubility and equilibrium Abstrak. Telah dilakukan penelitian tentang penerapan model inkuiri terbimbing pada pembelajaran materi kelarutan dan kesetimbangan larutan berbasis multi intelegensi di kelas XI IPA 7 SMA Negeri 1 Banjarmasin. Penelitian ini bertujuan untuk mengetahui peningkatan prestasi belajar siswa pada materi kelarutan dan Ksp, serta respon siswa pada pembelajaran menggunakan model inquiry terbimbing. Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan dalam 2 siklus. Tiap siklus terdiri dari tahap perencanaan, pelaksanaan tindakan, observasi dan evaluasi, serta analisis dan refleksi. Subjek penelitian adalah 22 siswa kelas XI IPA 7 SMA Negeri 1 Banjarmasin. Teknik pengumpulan data menggunakan tes dan observasi. Hasil penelitian menunjukkan bahwa prestasi belajar kimia siswa pada materi kelarutan dan kesetimbangan larutan menggunakan model inkuiri terbimbing meningkat secara signifikan. Penggunaan model inkuiri terbimbing meningkatkan ketuntasan hasil belajar kimia pada materi kelarutan dan kesetimbangan larutan dari siklus 1 sebesar 25 %, menjadi lebih 90 % pada siklus II. Skor aktivitas siswa meningkat dari 47 pada siklus I menjadi 52 pada siklus II dengan kriteria sangat aktif. Aktivitas guru meningkat dari skor 49 pada siklus I menjadi 52 pada siklus II dengan kriteria sangat aktif. Penggunaan model membuat siswa merasa lebih mudah memahami materi, terlibat sepenuhnya dalam pembelajaran, dan menumbuhkan rasa tanggung jawab terhadap tugas yang diberikan. Pembelajaran sangat menyenangkan dimana guru berperan sebagai fasilitator pembelajaran. Kata kunci: model Inquiri terbimbing, multi-intelegensi, Kelarutan dan Ksp